2010
DOI: 10.1016/j.cell.2010.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of the RIG-I Pathway Reveals a Signaling Role of Unanchored Polyubiquitin Chains in Innate Immunity

Abstract: SUMMARY RIG-I detects invading viral RNA and activates the transcription factors NF-κB and IRF3 through the mitochondrial protein MAVS. Here we show that RNA bearing 5′-triphosphate strongly activates the RIG-I–IRF3 signaling cascade in a reconstituted system composed of RIG-I, mitochondria and cytosol. Activation of RIG-I requires not only RNA, but also polyubiquitin chains linked through lysine-63 (K63) of ubiquitin. RIG-I binds specifically to K63 polyubiquitin chains through its tandem CARD domains in a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
638
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 542 publications
(660 citation statements)
references
References 35 publications
21
638
1
Order By: Relevance
“…This heterodimeric E2 has been reported to be one of the cognate E2s for TRIM25 and TRIM32, and thus, we used it to compare their ability to catalyse the formation of poly‐ubiquitin chains independent of the nature of the substrate (Zeng et al , 2010; Napolitano et al , 2011; Zhang et al , 2012). As observed in the discharge assays, the monomeric TRIM25 RING‐only and B‐box‐containing fragments are active (Figs 2E and F, and EV1), whereas TRIM32 only showed activity for dimeric constructs (Figs 2G and H, and EV1).…”
Section: Resultsmentioning
confidence: 99%
“…This heterodimeric E2 has been reported to be one of the cognate E2s for TRIM25 and TRIM32, and thus, we used it to compare their ability to catalyse the formation of poly‐ubiquitin chains independent of the nature of the substrate (Zeng et al , 2010; Napolitano et al , 2011; Zhang et al , 2012). As observed in the discharge assays, the monomeric TRIM25 RING‐only and B‐box‐containing fragments are active (Figs 2E and F, and EV1), whereas TRIM32 only showed activity for dimeric constructs (Figs 2G and H, and EV1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the group of Zhijian Chen developed a cell free system that reconstitutes the complete RIG-I signaling pathway from 5′-triphosphorylated RNA (5′-pppRNA) to IRF3 activation [6]. Hou et al have now used this powerful in vitro system to make the remarkable discovery that MAVS forms prion-like aggregates to propagate RIG-I signaling [7].…”
mentioning
confidence: 99%
“…It has been shown that the intact tandem CARDs are essential and sufficient for signaling [9,36,37], and mammalian RIG-I mutants with a CARD deletion or CARD point mutations (T55I or S183I) all function as a dominant inhibitor in its signaling [9,11,38]. It has also been revealed in mammals that the RIG-I downstream signaling via MAVS requires the recruitment of TRIM25 and other ubiquitination enzymes to synthesize unanchored K63-linked polyubiquitin chains binding to the CARD domains [36,37,39,40]. In the present study, RIG-Ia, the insertion variant of RIG-I with additional 38-aa residues in the CARD2 domain had no direct role in the activation of type I IFN promoter or antiviral defense, although the expression level of RIG-Ia could be induced under E. tarda or SVCV infections.…”
Section: Discussionmentioning
confidence: 99%